1999
DOI: 10.1007/s004320050287
|View full text |Cite
|
Sign up to set email alerts
|

The influence of l -triiodothyronine, l -thyroxine, estradiol-17β, the luteinizing-hormone-releasing hormone, the epidermal growth factor and gastrin on cell proliferation in organ cultures of 35 benign and 13 malignant human thyroid tumors

Abstract: Triiodothyronine, thyroxine, LHRH and gastrin may increase or decrease cell proliferation in human thyroid tissues, whether benign or malignant, to the same extent as other hormones and/or growth factors such as thyrotropin, EGF, insulin-like growth factor 1, transforming growth factor beta1 and estradiol the effects of which on thyroid cell proliferation are already well documented in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…These two studies suggest a preneoplastic nature of microfollicular adenomas. We reached the same conclusions by the identification of distinct glycan epitopes in thyroid adenomas, as opposed to thyroid carcinomas (22), and by the analysis of the influence of various growth factors and hormones on the cell proliferation of human thyroid tumors (51). These data, with conspicuously very different experimental designs, clearly suggest the preneoplastic nature of a set of thyroid adenomas that exhibit microfollicular histopathological characteristics.…”
Section: Discussionsupporting
confidence: 56%
“…These two studies suggest a preneoplastic nature of microfollicular adenomas. We reached the same conclusions by the identification of distinct glycan epitopes in thyroid adenomas, as opposed to thyroid carcinomas (22), and by the analysis of the influence of various growth factors and hormones on the cell proliferation of human thyroid tumors (51). These data, with conspicuously very different experimental designs, clearly suggest the preneoplastic nature of a set of thyroid adenomas that exhibit microfollicular histopathological characteristics.…”
Section: Discussionsupporting
confidence: 56%
“…The microfluidic system described herein uses precision cut tissue slices (PCTS) which maintain the multicellular 3D architecture of the thyroid tissue essential for intercellular communication, which is not well recapitulated in standard in vitro systems. Two previous studies have employed static culture of thyroid tissue explants: Russo et al [16] investigated apoptosis subsequent to 131 I treatment in 1mm 3 tissue fragments, whereas Nagy et al [17] examined the effect of various hormones and cytokines on the proliferation of 2mm 3 thyroid fragments. The results from these studies demonstrated that thyroid tissue cultured ex vivo can respond to external stimuli, however clinical utility was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic system described herein uses precision cut tissue slices (PCTS) which maintain the multicellular 3D architecture of the thyroid tissue essential for intercellular communication, which is not well recapitulated in standard in vitro systems. Two previous studies have employed static culture of thyroid tissue explants: Russo et al (16) investigated apoptosis subsequent to 131 I treatment in 1mm 3 tissue fragments, whereas Nagy et al (17) examined the effect of various hormones and cytokines on the proliferation of 2mm 3 thyroid fragments. The results from these studies demonstrated that thyroid tissue cultured ex vivo can respond to external stimuli, however clinical utility was not assessed.…”
Section: Introductionmentioning
confidence: 99%